2017
DOI: 10.1103/physrevb.96.155402
|View full text |Cite
|
Sign up to set email alerts
|

Heat radiation and transfer for point particles in arbitrary geometries

Abstract: We study heat radiation and heat transfer for pointlike particles in a system of other objects. Starting from exact many-body expressions found from scattering theory and fluctuational electrodynamics, we find that transfer and radiation for point particles are given in terms of the Green's function of the system in the absence of the point particles. These general expressions contain no approximation for the surrounding objects. As an application, we compute the heat transfer between two point particles in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 66 publications
1
45
1
Order By: Relevance
“…Our goal is to compute the HT from point particle 1 (PP 1) to point particle 2 (PP 2) in this system. We note that the point particle limit is valid if the radius of each particle is small compared to any other length scale in the system related to the particles [20], including thermal wavelength, skin penetration depth of each particle, the distance between the particles r, and the distance from each particle to a plate d 2 . In this limit, the multiple scatterings from the particles can be neglected and the particles can be modeled by the electrical dipole polarizability [20].…”
Section: Removing One Dimension: a Cavity Between Two Parallel Plmentioning
confidence: 99%
See 2 more Smart Citations
“…Our goal is to compute the HT from point particle 1 (PP 1) to point particle 2 (PP 2) in this system. We note that the point particle limit is valid if the radius of each particle is small compared to any other length scale in the system related to the particles [20], including thermal wavelength, skin penetration depth of each particle, the distance between the particles r, and the distance from each particle to a plate d 2 . In this limit, the multiple scatterings from the particles can be neglected and the particles can be modeled by the electrical dipole polarizability [20].…”
Section: Removing One Dimension: a Cavity Between Two Parallel Plmentioning
confidence: 99%
“…One of the most popular simplifications is the point particle limit where HR and HT are computed for pointlike particles [18][19][20][21][22]. In this case, it has been shown that the presence of an additional object can have a large effect on the heat exchange between the particles, including strong enhancements of the HT compared to the vacuum case [18][19][20][21][22]. Also, in this case, the boundary conditions can be described by the Green's function of the objects surrounding the particles [18,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have seen that the non-reciprocal surface modes have a strong impact in the heat flux rectification. Furthermore, it could be observed that the heat flux between the nanoparticles is strongly enhanced by the presence of the surface modes as already studied in reciprocal media [22][23][24][25][26][27][28][29][30]. The evident question is the following: Is this enhanced heat flux resulting in an enhanced heating effect?…”
Section: Mean Poynting Vectormentioning
confidence: 94%
“…Effects like the coupling to surface modes of a nearby substrate as studied in Refs. [46][47][48][49] are therefore neglected at this stage. Furthermore, we neglect the heat flux between the particles and the surrounding environment, which itself provides a heat flux channel, since this gives a negligible contribution when the particles are interacting in the near field [42].…”
Section: A Theoretical Frameworkmentioning
confidence: 99%